Heartbeat sound feature extraction and classification - Bibrity, Fariha Chowdhury; Jahan, Farhana; Khan, Md. Shahriar (Brac University, 2020)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Computer Science, 2019.